Grindability of plasma sprayed thermal barrier coating using super abrasive wheel. (2nd January 2020) - Kar, S.; Kumar, A. Sravan; Bandyopadhyay, P. P.; Paul, S.
ABSTRACT: Thermal Barrier Coatings (TBC) are commonly used on exhaust muffle of engines and gas turbine blades to protect the component from generated heat and increase the operational temperature. Machining of ceramic coatings is comparatively more challenging than sintered ceramics. In this study, a commonly used TBC coating, namely yttria stabilised zirconia coating was subjected to surface grinding using a mono layer nickel bonded diamond wheel. The grinding forces and specific grinding energy were studied experimentally. The normal force obtained experimentally was compared with a force model and the correlation was studied. The forces obtained were significantly low as compared to sintered YSZ and a close relationship was observed with the existing model. In addition, the specific grinding energy was also found to be minimum. This indicates that most of the energy is expended in ploughing, micro-brittle fracture and rubbing. This was ascertained through scanning electron images of the ground surface and the fragmented chips. X-Ray diffraction images of the ground sample and as-sprayed sample showed an insignificant change in material structure owing to the material removal mechanism. The surface roughness of the ground specimen was reduced significantly. The fracture toughness obtained using the Evans and Charles method was used to calculate the critical load for crack initiation and a significantly low value was observed for ductile to brittle transition. SEM images of ground chips of YSZ sample showed fragmented and broken chips indicating that the primary mode of material removal is owing to micro-brittle fracture.